Profile of currently employed European food scientists and technologists: education, experience and skills - Flynn, Katherine (2021)
The food and drink (F & D) sector in Europe ranks low in innovation and the European F & D industry has been losing importance in the global market. The food professionals, i.e., food scientists and technologists (FSTs), may not be meeting the varied demands of the sector. Here, education, experience and skills of current FSTs were identified and compared geographic regions and employment areas. Between 2009 and 2012, 287 questionnaires representing over 4000 FSTs were collected from employers in 16 countries. Analyses showed that more than 80% of FSTs have a university degree; but only in Industry in the Central European region are most degrees in food science/technology. More than half of FSTs, and almost 60% in the South, have less than 10 years' experience. The most common FST job title is Quality Manager, but with several variations based on region and employment area. Among skills, the most common is Communicating; found in over 90% of FSTs in all regions and employment areas. Food Safety is the most common of the food sector-specific skills, present in more than 75% of FSTs, yet there are differences in food sector skills based on employment area. Overall, these data suggest similarities among currently employed food professionals throughout Europe; they are young and highly educated, but also differences, especially in their food sector-specific skills. An understanding of the current FST should contribute to the improvement of FST training and thus benefit the European food sector.